Tourist guide expert system for Sarawak / Heldie Anak David - David, Heldie (Faculty of Computer and Mathematical Sciences, 2007)
Sarawak is the one of tiie biggest state in Malaysia, endowed with the worids' richest and most diverse ecosystem make it becomes one of the famous tourism destination around the worid. The problem is to recommend a suitable destination based on the interest and preference of the tourist. The weaknesses of current e-tourism application are its complexity in products and services they advertised. With the large quantity of information, tourist foimd it is hard to fmd destination that truly match with their interest and preference. Therefore, Tourist Guide Expert System will help the tourist to fmd destination that suitable with them. The objective is to find the characteristics of problem that affect decision making process, to apply Rule-Based Expert System technique in decision making and develop system that recommend destination to tourist based on their interests and preferences. Rules are produced as to represent the knowledge and converted into computer system using HTML and ASP as to provide a Web-based environment. The result of this project is rules that represent the knowledge and recommended destination for tourist. As the conclusion, this prototype system can be considered as a success development due to its ability to meet the objectives that has been set in early phase of project development. However, some improvement can still be made for the fixture expansion. Tourist Guide Expert System (For Sarawak) is a great application for solving the tourism problem that faces by most tourists.